The effect of pricing and labeling of cereal products on parent buying intentions / Norhidayu Rahim - Rahim, Norhidayu (2013)
Buying processes of healthy food involve many factors relating to the final decision of the consumers and those aspects influence consumer perceived value and their buying behavior on deciding which type of product they would buy. This study is attempted to gain knowledge about parent intentions towards buying cereal food products. With sample of 300 respondents, consist of parents from selective hypermarket in Kuala Lumpur, the data obtained from the survey were analyzed with reliability test, correlation, t-test and regression analysis. Result from this study indicated that parents are aware about what is happening to the health care of the children with regards to nutritional concerns. The findings indicated that price factor have more impact on parents buying intentions of cereal product rather than labeling factor. Both factors are significantly impact parents buying intentions however the strengths are not too high. It have been noticed that high-income parents more concern on price because they need to feel in a position to justify a product through other gains before they are willing to pay for the price. Hence, this study is expected to provide understanding on the reasons of buying and would probably help marketers of cereal food products to establish a proper communication message to different category of buyers who care much on their family healthy food consumption. The limitation of this study is that the sample was restricted to a single geographic area in Malaysia and one group of consumers. Future research should focus on extended scope to all states in Malaysia and may extend on other marketing aspects such as advertisement, sales promotions and customer relationship management.